Characterization of process and radiation induced defects in Si and Ge using conventional deep level transient spectroscopy (DLTS) and Laplace-DLTS - Auret, F.D. (Francois Danie) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.